Proteome Profiling of Populus euphratica Oliv. Upon Heat Stress - FERREIRA, SÍLVIA (Oxford University Press, 2006)
• Background and Aims Populus euphratica is a light-demanding species ecologically characterized as a pioneer. It grows in shelter belts along riversides, being part of the natural desert forest ecosystems in China and Middle Eastern countries. It is able to survive extreme temperatures, drought and salt stress, marking itself out as an important plant species to study the mechanisms responsible for survival of woody plants under heat stress. • Methods Heat effects were evaluated through electrolyte leakage on leaf discs, and LT(50) was determined to occur above 50 °C. Protein accumulation profiles of leaves from young plants submitted to 42/37 °C for 3 d in a phytotron were determined through 2D-PAGE, and a total of 45 % of up- and downregulated proteins were detected. Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF)/TOF analysis, combined with searches in different databases, enabled the identification of 82 % of the selected spots. • Key Results Short-term upregulated proteins are related to membrane destabilization and cytoskeleton restructuring, sulfur assimilation, thiamine and hydrophobic amino acid biosynthesis, and protein stability. Long-term upregulated proteins are involved in redox homeostasis and photosynthesis. Late downregulated proteins are involved mainly in carbon metabolism. • Conclusions Moderate heat response involves proteins related to lipid biogenesis, cytoskeleton structure, sulfate assimilation, thiamine and hydrophobic amino acid biosynthesis, and nuclear transport. Photostasis is achieved through carbon metabolism adjustment, a decrease of photosystem II (PSII) abundance and an increase of PSI contribution to photosynthetic linear electron flow. Thioredoxin h may have a special role in this process in P. euphratica upon moderate heat exposure.